PENGARUH KECUKUPAN MODAL, LOAN TO DEPOSIT RATIO, KONSENTRASI KEPEMILIKAN DAN UKURAN BANK TERHADAP KINERJA BANK UMUM - Nurzikri Lullah; Taswan Taswan; Penunjang Waruwu (Faculty of Economic and Business Universitas STIKUBANK, 2020)
This study aims to determine the performance of commercial banks as a dependent variable able to be influenced by the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Ownership Concentration and Bank Size as independent variables. This study uses a period of three years starting in 2016 to 2018 using Purposive Sampling as a sampling method. This research uses regression analysis. The results explained that bank performance was significantly affected by CAR and bank Size. Individually, ROA is positively and significantly affected by CAR and Company Size, and bank performance is not affected by LDR and Ownership Concentration. Keywords: capital adequacy ratio (CAR), loan to deposit ratio (LDR), ownership concentration, bank size, and bank performance